Peningkatan Ekonomi Masyarakat Berbasis Budidaya Ikan Nila Inovasi Bioflok di Desa Lipukasi Kecamatan Tanete Rilau Kabupaten Barru - G Gunawan; A Amiruddin; Abdul Majid; F Fatmasari; F Febriansyah; Erni Indrawati; Sitti Mujahidah; Seri Suriani; H Hasrif (Jurnal TUNAS, 2022)
Lipukasi Village, Barru Regency has enormous potential for marine and pond fish. Fishermen find it difficult to increase their income because they have to immediately sell their cultivation results to fish auctions with low bargaining power. The price of live fish is very low when fish are abundant, so farmers suffer losses because it is not worth the costs incurred for cultivation. The knowledge and skills of cultivating families are still low towards independent entrepreneurs, especially in increasing the added value of products and family income by diversifying food from fishery products. The characteristics of fish that are easily damaged and rotten cause farmers to have a dependence on immediately selling their cultivated products alive or fresh. This dependence can be overcome by carrying out the production process of processed food made from fish which can increase the durability and added value of products, especially fish which cannot be sold in fresh form. The development of independent entrepreneurs, especially fish processed food diversification, can increase the bargaining value and income of farming families. In an effort to increase income, the main obstacle faced by farmers and their families in conducting fish-based processed food entrepreneurship is not knowing and being skilled in processing standardized food, as well as doing fish processing and preservation business properly and in a variety according to market needs. The income of pond farmers can be increased by transferring technology, namely cultivating using biofloc, processing fish into processed fish products that are good and safe for consumption, including fish sausages, fish floss, and others. The results of this tavern are in the form of training, making biofloc, fish processing and self-employment.